Risk of COVID-19 Infection Among Medical Recorders: a Descriptive Study in Central Java Province (Association of Public Health Scholars based in Faculty of Public Health, Sriwijaya University, 2021)
Covid infection risks among non-medical staff in healthcare facilities may not be as high as physicians and nurses. However, healthcare facilities should understand infection risk among non-medical staff who works during the pandemic. This study describes several factors associated with Covid-19 infection among medical recorders. A descriptive study with a cross-sectional approach observed 124 medical record officers in Central Java Province from January to June 2021. This study measured socio-demographic factors, job characteristics, infection prevention and control (IPC) efforts, and Covid-19 infection through an online questionnaire with Kobotoolbox. Data analyze performed in descriptive and bivariate analysis. Most respondents said personal protective equipment (PPE) availability was adequate and had received IPC training. Socio-demographic factors, PPE availability, IPC training, and occupation were significantly unrelated to covid 19 infections. Having infected co-workers was related to covid 19 transmissions. Covid-19 cases proportion mostly in respondents who work in type C and D hospitals, never or rarely available PPE, received IPC training, worked <7 hours/day, and medical record staff. Healthcare facilities should pay more attention to PPE availability and other infection prevention and control for medical recorder staff. Further research should assess the contact history of workers with positive covid 19 both in or outside their workplace and their activities outside their workplace, PPE use compliance, and IPC training time.